Recent advances in transition metal-catalyzed Csp2-monofluoro-, difluoro-, perfluoromethylation and trifluoromethylthiolation - Landelle, Grégory; Panossian, Armen; Pazenok, Sergiy; Vors, Jean-Pierre; Leroux, Frédéric R. (Beilstein Journal of Organic Chemistry, 2013)
In the last few years, transition metal-mediated reactions have joined the toolbox of chemists working in the field of fluorination for Life-Science oriented research. The successful execution of transition metal-catalyzed carbon–fluorine bond formation has become a landmark achievement in fluorine chemistry. This rapidly growing research field has been the subject of some excellent reviews. Our approach focuses exclusively on transition metal-catalyzed reactions that allow the introduction of –CFH2, –CF2H, –CnF2n+1 and –SCF3 groups onto sp² carbon atoms. Transformations are discussed according to the reaction-type and the metal employed. The review will not extend to conventional non-transition metal methods to these fluorinated groups.
Keywords: catalysis; cross-coupling; difluoromethylation; fluorine; monofluoromethylation; organo-fluorine; transition metal; trifluoromethylation; trifluoromethylthiolation

Organofluorine Chemistry: Principles and Commercial Applications - Banks, R. E.; Smart, B. E.; Tatlow, J. C. (Plenum Press, 2000)

Organofluorine Compounds: Chemistry and Application - Hiyama, T.; Kanie, K.; Kusumoto, T.; Morizawa, Y.; Shimizu, M. (Springer-Verlag, 2000)

Modern Fluoroorganic Chemistry - Kirsch, P. (Wiley-VCH, 2004)

Fluorine in Organic Chemistry - Chambers, R. D. (Blackwell, 2004)

Organofluorine Chemistry - Uneyama, K. (Blackwell, 2006)

Bioorganic and Medicinal Chemistry of Fluorine - Bégué, J.-P.; Bonnet-Delpon, D. (John Wiley and Sons, 2008)

(untitled) - Purser, S.; Moore, P. R.; Swallow, S.; Gouverneur, V. (Chem. Soc. Rev., 2008)

Fluorine in Pharmaceutical and Medicinal Chemistry: From Biophysical Aspects to Clinical Applications - Gouverneur, V.; Muller, K. (Imperial College Press, 2012)

Fluorine In Medicinal Chemistry And Chemical Biology - Ojima, I. (John Wiley & Sons Ltd., 2009)

(untitled) - Müller, K.; Faeh, C.; Diederich, F. (Science, 2007)

(untitled) - Kirk, K. L. (J. Fluorine Chem., 2006)

(untitled) - Kirk, K. L. (Curr. Top. Med. Chem., 2006)

(untitled) - O'Hagan, D. (Chem. Soc. Rev., 2008)

(untitled) - Isanbor, C.; O’Hagan, D. (J. Fluorine Chem., 2006)

(untitled) - Jeschke, P.; Baston, E.; Leroux, F. R. (Mini-Rev. Med. Chem., 2007)

(untitled) - Leroux, F.; Jeschke, P.; Schlosser, M. (Chem. Rev., 2005)

(untitled) - Jeschke, P. (Pest Manag. Sci., 2010)

Modern Crop Protection Compounds - Kraemer, W.; Schirmer, U.; Jeschke, P.; Witschel, M. (Wiley-VCH Verlag GmbH & Co. KGaA, 2012)

Crop Protection Research - Jeschke, P.; Kraemer, W.; Schirmer, U.; Witschel, M. (Modern Methods, 2012)

(untitled) - Jeschke, P. (ChemBioChem, 2004)

(untitled) - Emsley, J. (Chem. Soc. Rev., 1980)

(untitled) - Liang, T.; Neumann, C. N.; Ritter, T. (Angew. Chem., Int. Ed., 2013)

(untitled) - Furuya, T.; Kamlet, A. S.; Ritter, T. (Nature, 2011)

(untitled) - Jin, Z.; Hammond, G. B.; Xu, B. (Aldrichimica Acta, 2012)

(untitled) - Liu, H.; Gu, Z.; Jiang, X. (Adv. Synth. Catal., 2013)

(untitled) - Sanford, M. S.; Ye, Y. (Synlett, 2012)

(untitled) - Tomashenko, O. A.; Grushin, V. V. (Chem. Rev., 2011)

(untitled) - Besset, T.; Schneider, C.; Cahard, D. (Angew. Chem., Int. Ed., 2012)

(untitled) - Bauer, H.; Fritz-Wolf, K.; Winzer, A.; Kühner, S.; Little, S.; Yardley, V.; Vezin, H.; Palfey, B.; Schirmer, R. H.; Davioud-Charvet, E. (J. Am. Chem. Soc., 2006)

(untitled) - Boehringer, M.; Fischer, H.; Hennig, M.; Hunziker, D.; Huwyler, J.; Kuhn, B.; Loeffler, B. M.; Luebbers, T.; Mattei, P.; Narquizian, R.; Sebokova, E.; Sprecher, U.; et al. (Biol. Med. Chem. Lett., 2010)

(untitled) - Oh, S.-J.; Lee, K. C.; Lee, S.-Y.; Ryu, E. K.; Saji, H.; Choe, Y. S.; Chi, D. Y.; Kim, S. E.; Lee, J.; Kim, B.-T. (Bioorg. Med. Chem., 2004)

(untitled) - Ahmed, V.; Liu, Y.; Taylor, S. D. (ChemBioChem, 2009)

(untitled) - Oishi, M.; Kondo, H.; Amii, H. (Chem. Commun., 2009)

(untitled) - Chu, L.; Qing, F.-L. (Org. Lett., 2010)

(untitled) - Litvinas, N. D.; Fier, P. S.; Hartwig, J. F. (Angew. Chem., Int. Ed., 2012)

(untitled) - Chen, Q.-Y.; Wu, S.-W. (J. Chem. Soc., Chem. Commun., 1989)

(untitled) - Liu, T.; Shao, X.; Wu, Y.; Shen, Q. (Angew. Chem., Int. Ed., 2012)

(untitled) - Cho, E. J.; Senecal, T. D.; Kinzel, T.; Zhang, Y.; Watson, D. A.; Buchwald, S. L. (Science, 2010)

(untitled) - Zhang, C.-P.; Wang, Z.-L.; Chen, Q.-Y.; Zhang, C.-T.; Gu, Y.-C.; Xiao, J.-C. (Angew. Chem., Int. Ed., 2011)

(untitled) - McLoughlin, V. C. R.; Thrower, J. (Tetrahedron, 1969)

(untitled) - Kobayashi, Y.; Kumadaki, I. (Tetrahedron Lett., 1969)

(untitled) - Hu, J.; Zhang, W.; Wang, F. (Chem. Commun., 2009)

(untitled) - Zhu, J.; Zhang, W.; Zhang, L.; Liu, J.; Zheng, J.; Hu, J. (J. Org. Chem., 2010)

(untitled) - Doi, H.; Ban, I.; Nonoyama, A.; Sumi, K.; Kuang, C.; Hosoya, T.; Tsukada, H.; Suzuki, M. (Chem.–Eur. J., 2009)

(untitled) - Beare, N. A.; Hartwig, J. F. (J. Org. Chem., 2002)

(untitled) - Guo, Y.; Twamley, B.; Shreeve, J. M. (Org. Biol. Chem., 2009)

(untitled) - Guo, C.; Wang, R.-W.; Guo, Y.; Qing, F.-L. (J. Fluorine Chem., 2012)

(untitled) - Guo, C.; Yue, X.; Qing, F.-L. (Synthesis, 2010)

(untitled) - Zhao, Y.; Ni, C.; Jiang, F.; Gao, B.; Shen, X.; Hu, J. (ACS Catal., 2013)

(untitled) - Tozer, M. J.; Herpin, T. F. (Tetrahedron, 1996)

(untitled) - Erickson, J. A.; McLoughlin, J. I. (J. Org. Chem., 1995)

(untitled) - Aráoz, R.; Anhalt, E.; René, L.; Badet-Denisot, M.-A.; Courvalin, P.; Badet, B. (Biochemistry, 2000)

(untitled) - Hope, H. R.; Heuvelman, D.; Duffin, K.; Smith, C.; Zablocki, J.; Schilling, R.; Hegde, S.; Lee, L.; Witherbee, B.; Baganoff, M.; Bruce, C.; Tall, A. R.; et al. (J. Lipid Res., 2000)

(untitled) - Giornal, F.; Pazenok, S.; Rodefeld, L.; Lui, N.; Vors, J.-P.; Leroux, F. R. (J. Fluorine Chem., 2013)

(untitled) - Manteau, B.; Pazenok, S.; Vors, J.-P.; Leroux, F. R. (J. Fluorine Chem., 2010)

(untitled) - Leroux, F. R.; Manteau, B.; Vors, J. P.; Pazenok, S. (Beilstein J. Org. Chem., 2008)

(untitled) - Fujikawa, K.; Fujioka, Y.; Kobayashi, A.; Amii, H. (Org. Lett., 2011)

(untitled) - Uneyama, K.; Mizutani, G.; Maeda, K.; Kato, T. (J. Org. Chem., 1999)

(untitled) - Amii, H.; Kobayashi, T.; Uneyama, K. (Synthesis, 2000)

(untitled) - Clavel, P.; Biran, C.; Bordeau, M.; Roques, N.; Trévin, S. (Tetrahedron Lett., 2000)

(untitled) - He, Z.; Luo, T.; Hu, M.; Cao, Y.; Hu, J. (Angew. Chem., Int. Ed., 2012)

(untitled) - Li, Z.; Cui, Z.; Liu, Z.-Q. (Org. Lett., 2013)

(untitled) - Studer, A. (Angew. Chem., Int. Ed., 2012)

(untitled) - Liu, T.; Shen, Q. (Eur. J. Org. Chem., 2012)

(untitled) - Samant, B. S.; Kabalka, G. W. (Chem. Commun., 2011)

(untitled) - Cho, E. J.; Buchwald, S. L. (Org. Lett., 2011)

(untitled) - Wang, X.; Truesdale, L.; Yu, J.-Q. (J. Am. Chem. Soc., 2010)

(untitled) - Zhang, X.-G.; Dai, H.-X.; Wasa, M.; Yu, J.-Q. (J. Am. Chem. Soc., 2012)

(untitled) - Zhang, L.-S.; Chen, K.; Chen, G.; Li, B.-J.; Luo, S.; Guo, Q.-Y.; Wei, J.-B.; Shi, Z.-J. (Org. Lett., 2013)

(untitled) - Loy, R. N.; Sanford, M. S. (Org. Lett., 2011)

(untitled) - Dudkina, Y. B.; Mikhaylov, D. Y.; Gryaznova, T. V.; Sinyashin, O. G.; Vicic, D. A.; Budnikova, Y. H. (Eur. J. Org. Chem., 2012)

(untitled) - Mu, X.; Chen, S.; Zhen, X.; Liu, G. (Chem.–Eur. J., 2011)

(untitled) - Weng, Z.; Lee, R.; Jia, W.; Yuan, Y.; Wang, W.; Feng, X.; Huang, K.-W. (Organometallics, 2011)

(untitled) - Knauber, T.; Arikan, F.; Röschenthaler, G.-V.; Gooßen, L. J. (Chem.–Eur. J., 2011)

(untitled) - Langlois, B. R.; Billard, T.; Roussel, S. (J. Fluorine Chem., 2005)

(untitled) - Kondo, H.; Oishi, M.; Fujikawa, K.; Amii, H. (Adv. Synth. Catal., 2011)

(untitled) - Billard, T.; Langlois, B. R.; Blond, G. (Tetrahedron Lett., 2000)

(untitled) - Matsui, K.; Tobita, E.; Ando, M.; Kondo, K. (Chem. Lett., 1981)

(untitled) - Chang, Y.; Cai, C. (J. Fluorine Chem., 2005)

(untitled) - Li, Y.; Chen, T.; Wang, H.; Zhang, R.; Jin, K.; Wang, X.; Duan, C. (Synlett, 2011)

(untitled) - Schareina, T.; Wu, X.-F.; Zapf, A.; Cotté, A.; Gotta, M.; Beller, M. (Top. Catal., 2012)

(untitled) - Shimizu, R.; Egami, H.; Nagi, T.; Chae, J.; Hamashima, Y.; Sodeoka, M. (Tetrahedron Lett., 2010)

(untitled) - Egami, H.; Shimizu, R.; Sodeoka, M. (Tetrahedron Lett., 2012)

(untitled) - Cai, S.; Chen, C.; Sun, Z.; Xi, C. (Chem. Commun., 2013)

(untitled) - Pair, E.; Monteiro, N.; Bouyssi, D.; Baudoin, O. (Angew. Chem., Int. Ed., 2013)

(untitled) - Ilchenko, N. O.; Janson, P. G.; Szabó, K. J. (Chem. Commun., 2013)

(untitled) - Wang, X.; Ye, Y.; Ji, G.; Xu, Y.; Zhang, S.; Feng, J.; Zhang, Y.; Wang, J. (Org. Lett., 2013)

(untitled) - Langlois, B. R.; Laurent, E.; Roidot, N. (Tetrahedron Lett., 1991)

(untitled) - Ji, Y.; Brueckl, T.; Baxter, R. D.; Fujiwara, Y.; Seiple, I. B.; Su, S.; Blackmond, D. G.; Baran, P. S. (Proc. Natl. Acad. Sci. U. S. A., 2011)

(untitled) - Bravo, A.; Bjørsvik, H.-R.; Fontana, F.; Liguori, L.; Mele, A.; Minisci, F. (J. Org. Chem., 1997)

(untitled) - Chu, L.; Qing, F.-L. (J. Am. Chem. Soc., 2012)

(untitled) - Jiang, X.; Chu, L.; Qing, F.-L. (J. Org. Chem., 2012)

(untitled) - Xu, J.; Luo, D.-F.; Xiao, B.; Liu, Z.-J.; Gong, T.-J.; Fu, Y.; Liu, L. (Chem. Commun., 2011)

(untitled) - Liu, T.; Shen, Q. (Org. Lett., 2011)

(untitled) - Huang, Y.; Fang, X.; Lin, X.; Li, H.; He, W.; Huang, K.-W.; Yuan, Y.; Weng, Z. (Tetrahedron, 2012)

(untitled) - Ye, Y.; Sanford, M. S. (J. Am. Chem. Soc., 2012)

(untitled) - Li, Y.; Wu, L.; Neumann, H.; Beller, M. (Chem. Commun., 2013)

(untitled) - Kamigata, N.; Fukushima, T.; Yoshida, M. (J. Chem. Soc., Chem. Commun., 1989)

(untitled) - Kamigata, N.; Fukushima, T.; Yoshida, M. (Chem. Lett., 1990)

(untitled) - Kamigata, N.; Fukushima, T.; Terakawa, Y.; Yoshida, M.; Sawada, H. (J. Chem. Soc., Perkin Trans. 1, 1991)

(untitled) - Kamigata, N.; Ohtsuka, T.; Fukushima, T.; Yoshida, M.; Shimizu, T. (J. Chem. Soc., Perkin Trans. 1, 1994)

(untitled) - Kamigata, N.; Ohtsuka, T.; Shimizu, T. (Phosphorus, Sulfur Silicon Relat. Elem., 1994)

(untitled) - Kamigata, N.; Ohtsuka, T.; Shimizu, T. (Sulfur Lett., 1994)

(untitled) - Kamigata, N.; Ohtsuka, T.; Yoshida, M.; Shimizu, T. (Synth. Commun., 1994)

(untitled) - Nagib, D. A.; MacMillan, D. W. C. (Nature, 2011)

(untitled) - Iqbal, N.; Choi, S.; Kim, E.; Cho, E. J. (J. Org. Chem., 2012)

(untitled) - Iqbal, N.; Choi, S.; Ko, E.; Cho, E. J. (Tetrahedron Lett., 2012)

(untitled) - Imhof, S.; Randl, S.; Blechert, S. (Chem. Commun., 2001)

(untitled) - Zhou, Q.-L.; Huang, Y.-Z. (J. Fluorine Chem., 1988)

(untitled) - Zhou, Q.-L.; Huang, Y.-Z. (J. Fluorine Chem., 1989)

(untitled) - Huang, X.-T.; Chen, Q.-Y. (J. Org. Chem., 2001)

(untitled) - Baciocchi, E.; Muraglia, E. (Tetrahedron Lett., 1993)

(untitled) - Mejia, E.; Togni, A. (ACS Catal., 2012)

(untitled) - Uraguchi, D.; Yamamoto, K.; Ohtsuka, Y.; Tokuhisa, K.; Yamakawa, T. (Appl. Catal., A, 2008)

(untitled) - Kino, T.; Nagase, Y.; Ohtsuka, Y.; Yamamoto, K.; Uraguchi, D.; Tokuhisa, K.; Yamakawa, T. (J. Fluorine Chem., 2010)

(untitled) - Parsons, A. T.; Senecal, T. D.; Buchwald, S. L. (Angew. Chem., Int. Ed., 2012)

(untitled) - Mizuta, S.; Stenhagen, I. S. R.; O’Duill, M.; Wolstenhulme, J.; Kirjavainen, A. K.; Forsback, S. J.; Tredwell, M.; Sandford, G.; Moore, P. R.; Huiban, M.; Luthra, S. K.; Passchier, J.; et al. (Org. Lett., 2013)

(untitled) - Kispert, L. D.; Liu, H.; Pittman, C. U. (J. Am. Chem. Soc., 1973)

(untitled) - Yu, D.; Gang, Z.; Weiyuan, H. (Tetrahedron Lett., 1993)

(untitled) - Iizuka, M.; Fukushima, S.; Yoshida, M. (Chem. Lett., 2007)

(untitled) - Iizuka, M.; Yoshida, M. (J. Fluorine Chem., 2009)

(untitled) - Wiehn, M. S.; Vinogradova, E. V.; Togni, A. (J. Fluorine Chem., 2010)

(untitled) - Schmidt, B. M.; Seki, S.; Topolinski, B.; Ohkubo, K.; Fukuzumi, S.; Sakurai, H.; Lentz, D. (Angew. Chem., Int. Ed., 2012)

(untitled) - Boiko, V. N. (Beilstein J. Org. Chem., 2010)

(untitled) - Zhang, C.-P.; Vicic, D. A. (J. Am. Chem. Soc., 2012)

(untitled) - Hansch, C.; Leo, A.; Taft, R. W. (Chem. Rev., 1991)

Substituent Constants for Correlation Analysis in Chemistry and Biology - Hansch, C.; Leo, A. (John Wiley and Sons, 1979)

(untitled) - Leo, A.; Jow, P. Y. C.; Silipo, C.; Hansch, C. (J. Med. Chem., 1975)

(untitled) - Hansch, C.; Leo, A.; Unger, S. H.; Kim, K. H.; Nikaitani, D.; Lien, E. J. (J. Med. Chem., 1973)

(untitled) - Manteau, B.; Genix, P.; Brelot, L.; Vors, J.-P.; Pazenok, S.; Giornal, F.; Leuenberger, C.; Leroux, F. R. (Eur. J. Org. Chem., 2010)

(untitled) - Tlili, A.; Billard, T. (Angew. Chem., Int. Ed., 2013)

(untitled) - Ferry, A.; Billard, T.; Bacqué, E.; Langlois, B. R. (J. Fluorine Chem., 2012)

(untitled) - Baert, F.; Colomb, J.; Billard, T. (Angew. Chem., Int. Ed., 2012)

(untitled) - Teverovskiy, G.; Surry, D. S.; Buchwald, S. L. (Angew. Chem., Int. Ed., 2011)

(untitled) - Chen, C.; Xie, Y.; Chu, L.; Wang, R.-W.; Zhang, X.; Qing, F.-L. (Angew. Chem., Int. Ed., 2012)

(untitled) - Tran, L. D.; Popov, I.; Daugulis, O. (J. Am. Chem. Soc., 2012)

(untitled) - Shao, X.; Wang, X.; Yang, T.; Lu, L.; Shen, Q. (Angew. Chem., Int. Ed., 2013)

(untitled) - Yang, Y.-D.; Azuma, A.; Tokunaga, E.; Yamasaki, M.; Shiro, M.; Shibata, N. (J. Am. Chem. Soc., 2013)